2015
DOI: 10.1002/ajhb.22752
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational changes in knee height among Maya mothers and their adult daughters from Merida, Mexico

Abstract: Objectives To analyze differences in knee height (KH) between adult Maya mothers and daughters in Merida City, Mexico, and determine if these differences are associated with their childhood socioeconomic conditions. Methods From September 2011 to January 2014, we measured KH and collected data on childhood conditions (place of birth, type of drinking water, family size, and fathers' occupation) from a sample of 180 Maya mother‐daughter dyads. Mean KH intergenerational difference was calculated and compared for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The change from thinness to fatness of Maya people is associated with nutrition and demographic transitions (Bogin et al, ). Our previous research reported that intergenerational effects contribute to perpetuating health problems in this population (Azcorra et al, ; Azcorra, Dickinson, et al, ; Azcorra, Rodríguez, et al, ; Varela‐Silva et al, ). A question remains as to when during the life cycle (fetus, infant, child, adolescent, and pregnant woman) the growth of the Maya is most sensitive to these environmental influences.…”
Section: Introductionmentioning
confidence: 79%
“…The change from thinness to fatness of Maya people is associated with nutrition and demographic transitions (Bogin et al, ). Our previous research reported that intergenerational effects contribute to perpetuating health problems in this population (Azcorra et al, ; Azcorra, Dickinson, et al, ; Azcorra, Rodríguez, et al, ; Varela‐Silva et al, ). A question remains as to when during the life cycle (fetus, infant, child, adolescent, and pregnant woman) the growth of the Maya is most sensitive to these environmental influences.…”
Section: Introductionmentioning
confidence: 79%
“…Number of siblings was recorded as the total number of offspring of a generation in the household as reported by the woman. Qualities of housing construction materials and family size have previously been shown to be sensitive indicators of childhood living conditions in a sample drawn from the same research project (Azcorra, Dickinson, Bogin, Rodriguez, & Varela‐Silva, ). The quality of house construction material was directly associated with the socioeconomic conditions of the family and provided indirectly an approximation of the parents' investment in offspring health and well‐being.…”
Section: Participants and Methodsmentioning
confidence: 96%
“…Particularly useful was the assistance received by grandmothers from their daughters and other relatives to understand our questions. The questionnaire was designed in such a way that several cross questions confirmed responses already given by the participants (Azcorra et al, ; Azcorra, Rodriguez, Varela‐Silva, Datta‐Banik, & Dickinson, ). Given these strategies, we believe that information on childhood living conditions provided by the participants was quite reliable.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…This is especially likely given the relatively muscular physiques of the stimuli, which might have diverted attention away from changes in IR; more generally, it is clear from figure 1 that the changes in IR are, like the changes in ABR, hard to detect—despite spanning a range from the lowest 0.1% of the population to the highest 0.1%. Thus, the slight preference for average IR broadly accords with the negative fitness correlates of short distal limbs [ 30 , 44 , 45 , 49 ], but, like for arm length, our data suggest that the ratio of the lower-to-upper-limb segments is not taken as a very important signal of fitness and has limited effect on mate choice.…”
Section: Discussionmentioning
confidence: 51%
“…for LBR and ABR) which, as described above, is linked to health. In addition, short distal limbs are associated with developmental stress and socioeconomic deprivation [ 30 , 44 , 45 , 49 ]. There are competing explanations for these effects, including the idea that shorter distal limbs represent an adaptation to the cold by reducing heat loss [ 45 ], the idea that distal limbs are more susceptible to reduced blood flow [ 50 ], and the ‘thrifty phenotype’ hypothesis under which certain tissues are sacrificed to ensure that more vital organs are preserved [ 30 , 51 ].…”
Section: The Influence Of Leg-to-body Ratio Arm-to-body Ratio and Inmentioning
confidence: 99%